Direct and Indirect Effects of Passion on Growing Technology Ventures. (4th May 2016) - Drnovsek, Mateja; Cardon, Melissa S.; Patel, Pankaj C.
Abstract : Research summary: Entrepreneurial passion has gained credence in recent years in explaining entrepreneurial efforts, yet examination of the dynamics of this emotion and its effects on venture growth is still in its infancy. Building on the literature on entrepreneurial motivation and entrepreneurial passion, we develop and test a model of entrepreneurial passion, goals, and venture growth. We utilize path analysis on a two‐wave sample of founders from 122 high technology firms. We find direct positive effects of passion for developing on venture growth and an indirect positive effect mediated by goal commitment, but not goal challenge. Implications for research and practice are discussed. Managerial summary: In this study, we show that entrepreneurs' positive feelings of entrepreneurial passion are positively associated with venture growth. We focus on a specific type of entrepreneurial passion—passion for developing a venture. Based on the findings from our study, we suggest that it is important for entrepreneurs to channel their passion for developing toward identifying challenging business goals and increasing commitment to business goals. We show that entrepreneurs who increase commitment toward business goals based on passion for developing realize higher venture growth. However, developing challenging goals based on passion does not lead to higher venture growth. Copyright © 2016 Strategic Management Society.